Conservation Tillage Mitigates Soil Organic Carbon Losses While Maintaining Maize Yield Stability Under Future Climate Change Scenarios in Northeast China: A Simulation of the Agricultural Production Systems Simulator Model - Hongrun Liu; Baocai Su; Rui Liu; Jiajie Wang; Ting Wang; Yijia Lian; Zhenzong Lu; Xue Yuan; Zhenwei Song; Runzhi Li (Agronomy)
Global warming may reduce maize yields and soil organic carbon (SOC), potentially threatening global food security and soil health. To address this concern in Northeast China, one of the world’s major maize production areas, the maize Agricultural Production Systems Simulator Model (APSIM) was used to evaluate how different tillage methods and straw return practices affect maize yields and SOC under future climate scenarios. The purpose of this study is to deal with the threat of global warming to the yield and SOC in the northeastern maize-producing areas, explore sustainable agricultural management strategies to stabilize the yield, enhance the soil carbon pool, counter the impact of climate change, and seek ways to ensure regional food and soil health. This study explored three tillage methods—plowing tillage (PT), rotary tillage (RT), and no-tillage (NT)—and two straw return methods—straw return (SR) and no straw return (SN)—under two Representative Concentration Pathway (RCP) scenarios: RCP4.5 and RCP8.5. The results showed that under the climate change scenarios: (1) For different tillage methods, no-tillage (NT) management showed the greatest increase in crop yield at 6.2%. SOC is highest under NT in the 0–20 cm soil layer under both straw return methods and climate scenarios. (2) For different straw return methods, SOC decreases when the straw is removed (SN) but increases when the straw is returned (SR) in both scenarios. Soil organic carbon density (SOCD) declines but can be mitigated by straw return. (3) Overall, tillage and straw return practices can significantly impact SOC under RCP4.5 but not under RCP8.5. Tillage and straw return practices together explain more than 50% yield changes under climate change scenarios. Through the modeling approach, this study revealed the potential benefits of integrating tillage and straw management practices to sustain maize yields and SOC. These practices can mitigate long-term climate change impacts on crop yields and soil health.